Clinical pharmacokinetics of aztreonam in cancer patients. - Jones, P G (1984)
The pharmacokinetics of aztreonam were studied in 25 adult patients with hematological malignancies. Two groups of nine patients each received aztreonam (1 or 2 g every 8 h) prophylactically, and seven infected patients received a therapeutic regimen of aztreonam (1.5 g every 4 h). The mean peak serum concentration after a 1-g dose of aztreonam (given over 0.5 h on day 1) was 75.5 micrograms/ml; after a 2-g dose it was 177.2 micrograms/ml. The mean peak serum concentration after a 1.5-g dose of aztreonam (given over 2 h on day 1) was 68.5 micrograms/ml. The serum half-life ranged between 1.7 and 2.0 h for all regimens studied. The urinary concentration of the metabolite of aztreonam, SQ 26,992, increased during 1 week of administration of the drug; however, serum levels of the metabolite were barely detectable.